1994
DOI: 10.1007/bf02076186
|View full text |Cite
|
Sign up to set email alerts
|

Double-stapled vs. handsewn ileal pouch-anal anastomosis in patients with chronic ulcerative colitis

Abstract: Double-stapled IPAA appears to convey no early functional advantage over handsewn IPAA for chronic ulcerative colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(25 citation statements)
references
References 22 publications
1
23
1
Order By: Relevance
“…17 The majority of patients would be satisfied by a daily stool frequency of less than six times after the pouch operation. 15 Although McIntyre et al reported that IACA had no early functional advantage over IPAA, the incidence of night-time incontinence was over 40% in each group, 18 being about twice as high as of our results.…”
Section: Discussioncontrasting
confidence: 54%
“…17 The majority of patients would be satisfied by a daily stool frequency of less than six times after the pouch operation. 15 Although McIntyre et al reported that IACA had no early functional advantage over IPAA, the incidence of night-time incontinence was over 40% in each group, 18 being about twice as high as of our results.…”
Section: Discussioncontrasting
confidence: 54%
“…The decreased continence likely relates to repeated sphincter trauma, 26,27 and may also be in part attributable to the mucosectomy and handsewn anastomosis required in the reconstruction group, which some authors believe contributes to decreased continence, 28,29 although this is disputed by others. [30][31][32] The increased number of bowel movements may be secondary to decreased total small bowel length in those patients who underwent pouch excision with construction of a new pouch. Twenty-two percent of patients with a new pouch in our study had more than ten bowel movements per day, compared with only 5.5 percent whose old pouch was reused.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3] The hypothesis was that because the ATZ preserved anal sensation, fecal incontinence would improve. Although several nonrandomized studies supported better functional results with this technique, 2-6 three prospective, randomized trials [19][20][21] and one case control study 22 found no significant functional difference.…”
Section: Discussionmentioning
confidence: 99%